2015
DOI: 10.3354/meps11107
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community structure in the river‑influenced continental margin of the northern Gulf of Mexico

Abstract: Phytoplankton community composition was characterized over varying seasonal and river discharge conditions during 5 research cruises across the continental margin of the northern Gulf of Mexico (NGOM). The spatial and temporal patterns of variation in the composition of the algal community were examined using high performance liquid chromatography (HPLC) analyses of phytoplankton pigments in conjunction with classification using the CHEMTAX software (v.1.95). Cluster analysis and principal component analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 47 publications
9
58
0
Order By: Relevance
“…A large number of hot spots were identified in margin surface waters and they exhibited substantial spatial and temporal variability, reflecting the productive and dynamic nature of this ecosystem. Hot spots frequently occurred at mid‐salinities (26–29) on the inner shelf, where high phytoplankton biomass and production are often observed during most seasons (Redalje et al ; Chakraborty and Lohrenz ). Interestingly, unlike neutral sugar hot spots, amino acid‐rich hot spots were mostly identified in waters collected during low‐ and no‐light time periods, suggesting diel variability in the source of labile DOM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A large number of hot spots were identified in margin surface waters and they exhibited substantial spatial and temporal variability, reflecting the productive and dynamic nature of this ecosystem. Hot spots frequently occurred at mid‐salinities (26–29) on the inner shelf, where high phytoplankton biomass and production are often observed during most seasons (Redalje et al ; Chakraborty and Lohrenz ). Interestingly, unlike neutral sugar hot spots, amino acid‐rich hot spots were mostly identified in waters collected during low‐ and no‐light time periods, suggesting diel variability in the source of labile DOM.…”
Section: Discussionmentioning
confidence: 99%
“…Hot spots with labile DOM enriched in amino acids showed distinct spatial distributions from those with carbohydrate‐rich labile DOM, indicating compositional variability in labile plankton DOM. Amino acid‐rich hot spots were found at relatively few locations, and they mostly occurred on the inner shelf where concentrations of nutrients and chlorophyll were high (Chakraborty and Lohrenz ). A few amino acid hot spots appeared further south near the shelf‐edge in March, coinciding with a widespread nutrient‐rich plume that resulted in elevated concentrations of chlorophyll across outer shelf and slope waters (Huang et al ; Chakraborty and Lohrenz ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discharge from both Mississippi and Atchafalaya Rivers strongly influences the distribution of dissolved and particulate material [ D'Sa and DiMarco , ; D'Sa et al ., ], nutrients [ Lehrter et al ., ; Turner et al ., ], and the availability and spectral properties of light [ Schaeffer et al ., ]. In conjunction with the large environmental gradients, our prior research has demonstrated substantial variations in phytoplankton communities across different water mass types and over seasonal time scales in these continental shelf waters [ Chakraborty and Lohrenz , ]. A recent study [ Zhao and Quigg , ] in a shallow inner shelf region of the NGOM also highlighted the importance of phytoplankton community composition in understanding the diel patterns of photosynthesis and photoacclimation under the complicated light and nutrient conditions.…”
Section: Introductionmentioning
confidence: 99%